2017
DOI: 10.20471/dec.2017.53.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Alcohol in Croatian Social Reality Alcohol as Part of Interaction Ritual Chain

Abstract: -Article is exploring the phenomena of interactional ritual chains of everyday life. Primarily, focus is on social interaction and integration of an individual in Croatia. We are going to use the basic premises of micro-sociological analysis of which in the center of attention is the theory of Randal Collins, symbolic interactionism and phenomenology. According to mentioned aspects, the paper analyzes the usage of alcohol in Croatia, which is basically traditionally organized. The main premise of this work is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…No one consumes alcohol until they have learned how and why to do it. When speaking of this learning of drinking patterns, it may also be a matter of primary socialisation, when the child watches adult in-teractions in which alcohol consumption occurs (among other things), and/or secondary socialisation factors, where alcohol consumption is part of an interaction ritual chain (see Brezovec, 2017). Thus, by considering the individual practice of alcohol consumption, the social foundations of this phenomenon are also considered.…”
Section: The Principle Of Methodological Individualism In the Sociolo...mentioning
confidence: 99%
“…No one consumes alcohol until they have learned how and why to do it. When speaking of this learning of drinking patterns, it may also be a matter of primary socialisation, when the child watches adult in-teractions in which alcohol consumption occurs (among other things), and/or secondary socialisation factors, where alcohol consumption is part of an interaction ritual chain (see Brezovec, 2017). Thus, by considering the individual practice of alcohol consumption, the social foundations of this phenomenon are also considered.…”
Section: The Principle Of Methodological Individualism In the Sociolo...mentioning
confidence: 99%
“…Drinking alcoholic beverages is one of the oldest forms of socially acceptable behavior which may result in alcohol addiction, one of the leading public health issues [1]. According to the extent of drinking and habits we differentiate social (controlled) drinking, alcohol abuse and alcohol addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Significance of sociodemographic factors in cognitive and emotional functioning of an alcohol addict and in motivation for abstinence has been found in many studies. Generally, it has been found that risk factors for negative outcomes in addiction treatment are male gender, younger age, unemployment, low education and divorce or never married individuals [26][27][28]7]. Howewer, results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%